Developments of Microstrip patch array antenna for wireless local area network (WLAN) - Azizan, Mat Hashim (Universiti Malaysia Perlis, 2008)
In this project, a 4x1 Rectangular Microstrip Patch Array Antenna at frequency 2.45 GHz for Wireless Local Area Network (WLAN) will be designed, fabricated and tested. The antenna will be design base on optimization and characteristics analysis. Some methods for optimize the Microstrip Patch Antenna are studied and implemented to produce the desired antenna. The objective of this project is to develop the antenna that has higher gain, higher directivity, wide bandwidth and higher efficiency. Theoretically, the objective of this project can be achieve through the use of high quality substrate such as RT Duroid 5870 which is have low relative permittivity or dielectric constant and higher substrate that will improve the bandwidth. This is due to the Rectangular Microstrip Patch Array Antenna which the bandwidth is determined by the dielectric constant and the height of substrate. Low loss-tangent will increase the efficiency of the antenna. The patch array also has a better directivity than the single patch. Microwave Office (MWO) will be introduce as an effective tool for modeling electromagnetic structure. The antenna was fabricated based on simulation and measured using Wave and Antenna Training System (WATS2002). The expected result from this project is the antenna will has a high gain, better directivity, larger bandwidth and high efficiency.